2007
DOI: 10.1634/stemcells.2007-0158
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Donor in the Repair of the Marrow Vascular Niche Following Hematopoietic Stem Cell Transplant

Abstract: STEM CELLS 2007;25:2945-2955 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 54 publications
(64 reference statements)
3
43
1
Order By: Relevance
“…53 Interestingly, we found that transplanted ECs did not engraft directly in the BM vasculature, but rather engrafted temporarily in the lungs of recipient mice, suggesting that soluble factors were elaborated by infused ECs, which promoted vascular and HSC regeneration. 53 In keeping with these findings, Slayton et al 54 demonstrated that, following BM transplantation, reconstitution of the BM vasculature derives predominantly from host ECs rather than donor-derived endothelial progenitor cells.…”
Section: Do Ecs Secrete Soluble Growth Factors That Mediate Hsc Self-mentioning
confidence: 85%
“…53 Interestingly, we found that transplanted ECs did not engraft directly in the BM vasculature, but rather engrafted temporarily in the lungs of recipient mice, suggesting that soluble factors were elaborated by infused ECs, which promoted vascular and HSC regeneration. 53 In keeping with these findings, Slayton et al 54 demonstrated that, following BM transplantation, reconstitution of the BM vasculature derives predominantly from host ECs rather than donor-derived endothelial progenitor cells.…”
Section: Do Ecs Secrete Soluble Growth Factors That Mediate Hsc Self-mentioning
confidence: 85%
“…It was reported previously that the BM sinusoidal system was compromised after 5-FU treatment or irradiation; the transplanted donor stem cells were involved in the reconstruction of a normal sinusoid system. 34,35 Accordingly, in post-5-FU Cxcl12-deficient BM, the preferential localization of HSPCs in the perisinusoidal space might contribute to the quicker rebuild of a vasculaturerelated environment for hematopoiesis. Compared with the wildtype mice, Cxcr4-deficient mice had a low survival rate after serial doses of 5-FU challenge, 8,13 while the same challenge did not result in a significant survival difference in Cxcl12-deficient mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence also supports the fact that microenvironmental cells and especially endothelial cells could be transplanted successfully and participate in the repair of the marrow vascular niche following stem cell transplantation. 97,98 Therefore, by participating in the recovery of a physiological regulatory environment, cellsincluding mesenchymal and/or endothelial cells provided by the healthy donor-would favor extinction of the clonal hematopoiesis to the benefit of the normal hematopoiesis.…”
Section: Conclusion and Therapeutic Challengementioning
confidence: 99%